Commercial and consumer law - Chuah, Jason; Furmston, Michael; Willett, Chris (Pearson, 2010)
This volume contains summaries of the essential cases & extracts from key legislative provisions that you will need to draw upon when answering problem or essay questions. Debate & issue boxes are included to highlight contentious areas of the law & help you refine your critical analysis skills.